Cocoa pulp as a novel source of plant-derived exosome-like nanovesicles: method comparison and physicochemical characterization - Tapia-Aguayo, Andrea; Krüger, Stephanie; Wessjohann, Ludger A.; Chica, María José; Hinderberger, Dariush; Volmer, Jonas; González-Valdez, José; Ramos-Parra, Perla A.; Fernández-Niño, Miguel (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionCocoa (Theobroma cacao L.) processing generates substantial agricultural residues, including pod husks and mucilaginous pulp, which remain largely underutilized. In this study, we report for the first time the isolation of plant-derived exosome-like nanovesicles (PENs) from cocoa pulp, a novel biological matrix with potential applications in sustainable nanobiotechnology.MethodsTwo primary cell disruption methods, high-performance homogenization and cryogenic grinding, were compared for PEN recovery, followed by ultracentrifugation-based purification. The vesicles were characterized by cryo-transmission electron microscopy (Cryo-TEM), dynamic light scattering (DLS), and bicinchoninic acid (BCA) protein assays.ResultsPENs isolated via cryogenic processing exhibited more uniform size distributions (111.9 ± 2.4 nm) and spherical morphology compared to those obtained by homogenization (120.2 ± 5.5 nm). While homogenization yielded higher protein concentrations, it also resulted in greater vesicle heterogeneity. No vesicles were detected from cocoa pod husks under the tested conditions.ConclusionThese findings establish cocoa pulp as a promising and sustainable source of PENs and demonstrate how primary recovery methods critically influence vesicle quality. This methodological contribution lays the groundwork for future studies on PEN bioactivity, cargo profiling, and functional applications.